Solar Cells: Quantifying Quasi‐Fermi Level Splitting and Mapping its Heterogeneity in Atomically Thin Transition Metal Dichalcogenides (Adv. Mater. 25/2019). Issue 25 (18th June 2019) - Tebyetekerwa, Mike; Zhang, Jian; Liang, Kun; Duong, The; Neupane, Guru Prakash; Zhang, Linglong; Liu, Boqing; Truong, Thien N.; Basnet, Rabin; Qiao, Xiaojing; Yin, Zongyou; Lu, Yuerui; et al.
Abstract : Two‐dimensional atomically thin transition metal dichalcogenides (TMDs) show a remarkable light–matter interaction and atomic thickness. In article number 1900522, Mike Tebyetekerwa, Yuerui Lu, Daniel Macdonald, Hieu T. Nguyen, and co‐workers quantify the possible maximum open‐circuit voltages, one of the most important photovoltaic parameters, of monolayer TMD‐based solar cells. The values they determine reveal the potential of atomically thin TMDs for high‐voltage, ultralight, flexible, and eye‐transparent future photovoltaic devices.